2016
DOI: 10.1007/s10545-016-9959-4
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibitors rescue premature lethality and attenuate dysregulation of GABAergic/glutamatergic transcription in murine succinate semialdehyde dehydrogenase deficiency (SSADHD), a disorder of GABA metabolism

Abstract: Recent studies have identified a role for supraphysiological GABA in the regulation of mTOR (mechanistic target of rapamycin), a protein kinase with pleiotropic roles in cellular development and homeostasis, including integration of growth factors and nutrient sensing, and synaptic input in neurons (Lakhani et al 2014; Vogel et al 2015). Aldehyde dehydrogenase 5a1-deficient (aldh5a1−/−) mice, the murine orthologue of human succinic semialdehyde dehydrogenase deficiency (SSADHD), manifest increased GABA that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 41 publications
4
37
1
Order By: Relevance
“…This has been confirmed by a number of investigators in the knockout mouse model (Gibson et al 2006; Latini et al 2007; Vogel et al, in press). Moreover, Sauer and colleagues (2007) extended these findings to demonstrate significant disruptions of enzyme complexes involved in mitochondrial oxidative metabolism in brain tissues derived from SSADHD knockout mice, which lends additional credence to the potential disruptive nature of DHHA in mitochondrial metabolism.…”
Section: Pathophysiological Mechanisms In Ssadhdmentioning
confidence: 62%
“…This has been confirmed by a number of investigators in the knockout mouse model (Gibson et al 2006; Latini et al 2007; Vogel et al, in press). Moreover, Sauer and colleagues (2007) extended these findings to demonstrate significant disruptions of enzyme complexes involved in mitochondrial oxidative metabolism in brain tissues derived from SSADHD knockout mice, which lends additional credence to the potential disruptive nature of DHHA in mitochondrial metabolism.…”
Section: Pathophysiological Mechanisms In Ssadhdmentioning
confidence: 62%
“…Further, we examined the capacity of newer generation drugs (Tor 1, Tor 2) that inhibit mTOR signaling to improve mRNA levels corresponding to these genes (Tables 1, 2). Additional rationale for examining the molecular aspects (mRNA levels) related to Tor 1 and Tor 2 intervention in aldh5a1 −/− mice derived from our finding that these agents are capable of significantly extending the lifespan of these mice [32]. …”
Section: Resultsmentioning
confidence: 99%
“…Armed with the preceding metabolic evidence for oxidative stress in aldh5a1 −/− mice, we opted to pursue a global assessment of both mTOR signaling and oxidative stress employing gene expression analysis for mRNA levels. Our rationale for these studies centered on earlier work with GABA, mTOR and oxidative stress [1, 13, 32], in which we showed that elevated GABA, acting via mTOR, induced accumulation of mitochondria and enhanced oxidative stress. The finding that rapamycin could mitigate these effects led us to investigate newer generation mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have highlighted alterations in GABAergic neurotransmission in SSADHD (Pearl et al 2009; Reis et al 2012; Buzzi et al 2006), both in the orthologue mouse model and patients, and it may be reasonable to assume that high levels of GABA and GHB during ontogeny induces an altered balance between GABAergic/GHBergic neurotransmission with that of excitatory glutamatergic neurotransmission (Jansen et al 2008; Vogel et al 2016; Talaei et al 2016). Our prediction is that as levels of GABA and GHB fall with age, this balance is likely disrupted and correlates with neuropsychiatric morbidity in patients.…”
Section: Discussionmentioning
confidence: 99%